Research on Cognitive Radio Non-orthogonal Multiple Access System in 5G Communications Oriented to Ubiquitous Power Internet of Things - Rui SHE; Ningchi ZHANG; Yanru WANG; Dandan GUO; Wenjie MA; Hui LIU; Jie ZHANG (Zhongguo dianli)
With the continuous advancement of the construction of the power Internet of Things, the power distribution network has seen exponential growth of data volume. As a result, the traditional smart power communication network based on cognitive radio is no longer capable of meeting the high demand for spectrum resources by a large number of devices that are installed to collect power consumption data. This paper constructs a 5G network model for the power Internet of Things, which aims to use the non-orthogonal transmission characteristics of non-orthogonal multiple access (NOMA) technology to further improve the spectrum resource utilization of the limited power private network. To ensure the accuracy of spectrum detection, a multi-user cooperative sensing method is adopted. The closed expressions of spectrum access probability and throughput are derived; in order to further increase the accuracy of the classification results, an improved K-means algorithm is proposed. The alternate iterative algorithm is implemented to jointly optimize the detection time, node power and the number of user clusters such that the system throughput can be maximized eventually. The simulation results show that compared with the traditional orthogonal multiple access system, not only the spectrum utilization but also the accuracy of the sensing results are significantly improved.